Protein sources for crossbred dairy cows in the semiarid - Viviany Lúcia Fernandes dos Santos (Revista Brasileira de Zootecnia, 2012)
Alternative sources of protein for lactating cows were evaluated in this study with respect to intake, digestibility, milk yield and milk composition. Eight multiparous Holstein/Gyr cows were simultaneously distributed in two 4 × 4 latin squares. Each experimental period lasted 21 days (14 days for adaptation and seven days to collect data and samples). Three protein sources, cottonseed meal, semi-integral soybean meal and corn steep liquor were evaluated and soybean meal was used as a control. When the corn steep liquor was used, lower intakes of dry matter, organic matter, crude protein and total digestible nutrients were observed compared with soybean meal. Animals that consumed corn steep liquor had a lower milk yield than those fed soybean meal, and no treatment effect on the milk fat content was detected. Animals that consumed cottonseed meal and corn steep liquor had a lower fat yield than those fed soybean meal. Feeding with semi-integral soybean meal decreased the milk protein percentage compared with soybean meal. Nutrient digestibility was lower for cows fed diets with corn steep liquor, except for crude protein digestibility, which was higher for animals fed cottonseed meal and semi-integral soybean meal compared with those fed soybean meal. Based on the dry matter intake, milk yield and milk components, soybean meal can be replaced with semi-integral soybean meal.